An AAC Mobile-Based Application for People with Intellectual Disability: A Case Study in Brazil. (5th June 2020) - Conte, Mauro José; Gomes Ferreira, Marcelo Gitirana; Ramírez, Alejandro R. García
Abstract : Augmentative and Alternative Communication (AAC) techniques are employed to mediate communication with people who have communication disorders, as in cases of intellectual disability. Although there are various digital solutions that promote alternative communication options for individuals with communication disorders, only a few of them have been specifically designed or targeted to people with intellectual disability (ID). This work is motivated by the lack of AAC solutions contributing to the rehabilitation processes of individuals with intellectual disability in Brazil. The study presents a mobile-based AAC solution conceived as a tool to assist the rehabilitation process of people with ID. The design was based on user-centered design principles and accessibility standards. The System Usability Scale (SUS) questionnaire was used to evaluate the solution. Four specialists and twenty-five students participated in this study. The proposed solution shows the potential educational value for professionals who assist individuals with intellectual disability in Brazil.